2003
DOI: 10.2214/ajr.180.5.1801271
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Multidetector CT in the Preoperative Evaluation of Patients with Renal Cell Carcinoma

Abstract: High-resolution MDCT is accurate in the preoperative evaluation of patients with renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(98 citation statements)
references
References 36 publications
(38 reference statements)
4
85
0
8
Order By: Relevance
“…Delayed images to show resolution of the filling defect are usually sufficient to confirm the artifactual nature of such pseudothrombosis [39]. High resolution MDCT protocol was proved to be correct in identification of thrombus in renal vein and IVC, with the higher radiation dose to the patient as a main drawback [40].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed images to show resolution of the filling defect are usually sufficient to confirm the artifactual nature of such pseudothrombosis [39]. High resolution MDCT protocol was proved to be correct in identification of thrombus in renal vein and IVC, with the higher radiation dose to the patient as a main drawback [40].…”
Section: Discussionmentioning
confidence: 99%
“…17 Catalona ve arkadaşları çalışmalarında çoklu dedektörlü BT %95 doğrulukla evreleme yaptıklarını bildirmişlerdir. 18 Çalışmamızda çoklu dedektörlü BT kullanılarak % 75 oranında doğru evreleme yaptığımızı bulduk.…”
Section: Discussionunclassified
“…Comparing with the spiral CT used before, MDCT has proved to have higher spatial resolution and better anatomy detail delineation. Catalano reported that MDCT had 95% accuracy for perinephric fat infiltration with sensitivity of 96% and specificity of 93% (7). However, even with MDCT and three dimensional technology, Hallscheidt and Türkvatan suggested the evaluation of renal tumor extension in to perinephric fat remains a difficult task (14,15).…”
Section: Discussionmentioning
confidence: 99%